Impact of FDI on Lithuanian economy: Insight into development of main economic activities - Tvaronavičienė, Manuela; Grybaitė, Virginija (Journal of Business Economics and Management, 2007)
Aim of the paper is to estimate impact of foreign direct investment (FDI) on growth of economy in Lithuania. In order to detect specifics of development of main economic activities, differences in structure of FDI and structure of GDP of host economy are being juxtaposed, FDI intensity indicator in main economic activities elaborated. Authors test if different levels of penetration of foreign capital into certain economic activities serve as important factor affecting their economic growth. Research is being developed further by making assumption about higher concentration of FDI intensive economic activities. Higher concentration in that context would be interpreted as possible crowding out of local business firms from FDI intensive industries. First Published Online: 14 Oct 2010